Varsity students use coconut shells to assist needy - Borneo Post, (KK) (Borneo Post, 2017)
Kuala Lumpur Heaps of discarded cocunut shells caught yhe attaention of a group of Universiti Utara Malaysia(UUM) student in Kedah, prompting them to take the initiative to recycle the"worthless" garbage as charcoal.